2015
DOI: 10.1038/srep16766
|View full text |Cite
|
Sign up to set email alerts
|

Type of in vitro cultivation influences cytoadhesion, knob structure, protein localization and transcriptome profile of Plasmodium falciparum

Abstract: In vitro cultivation of Plasmodium falciparum is critical for studying the biology of this parasite. However, it is likely that different in vitro cultivation conditions influence various aspects of the parasite’s life cycle. In the present study two P. falciparum isolates were cultivated using the two most common methods, in which AlbuMAX or human serum as additives are used, and the results were compared. The type of cultivation influenced the knob structure of P. falciparum-infected erythrocytes (IEs). IEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Finally, adherent IEs are counted manually. These experiments demonstrated that laboratory-adapted trophozoite-stage IT4 and 3D7 isolates show different binding capacities to various ECRs under static conditions 31,33 . The main objective of this study was to characterize the binding behavior of erythrocytes infected with P. falciparum to the ECRs CD36, ICAM-1, P-selectin, CD9, and CSA under controlled flow and temperature conditions.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, adherent IEs are counted manually. These experiments demonstrated that laboratory-adapted trophozoite-stage IT4 and 3D7 isolates show different binding capacities to various ECRs under static conditions 31,33 . The main objective of this study was to characterize the binding behavior of erythrocytes infected with P. falciparum to the ECRs CD36, ICAM-1, P-selectin, CD9, and CSA under controlled flow and temperature conditions.…”
Section: Resultsmentioning
confidence: 84%
“…Experimental setup. Endothelial cytoadhesion and the binding capacities of various laboratory strains and patient isolates of P. falciparum have been mainly investigated under static conditions 6,31,32 . This is classically achieved by directly incubating IEs with cells or recombinant receptors of interest 8,16,33,34 .…”
Section: Resultsmentioning
confidence: 99%
“…Keeping in mind the above‐mentioned challenges, we first decided to use the parasite cultivation method that allows formation of maximum numbers of knobs on the erythrocyte membrane. It has been demonstrated that long‐term in vitro cultivated parasites form a lower number of knobs, and that the use of the medium supplement AlbuMAX alone in the culture media results in fewer knobs on the surface of iRBC as compared to 10% human serum . Therefore, we used a 3D7 knobby line (validated by punctate staining of KAHRP on the infected erythrocyte membrane by immunofluorescence; Supporting Information Figure S1) that was in culture for a short while and maintained it in media containing 10% human serum instead of AlbuMAX.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Albumax (Life Technologies, Paisley, United Kingdom) was used to grow the parasites. Compared to the use of human serum, parasites grown with Albumax display altered expression of over 500 genes (31). For example, the cytoadhesion of infected RBCs to various endothelial receptors is greatly reduced in the presence of Albumax compared to human serum.…”
Section: Discussionmentioning
confidence: 99%